Evaluation of the antiproliferative potential of Cocos nucifera juice - Enegide Chinedu; Ifeoma Agatha Onah; Paul Okesinachi Amaje; Dabum Luka Jacob (Shahrekord University of Medical Sciences, 2018)
Introduction: The World Health Organization has predicted that the death caused by cancer may rise to a high rate of about 11.5 million in the year 2030. Cocos nucifera juice (Coconut water) is a known refreshing and nutritious beverage which is widely consumed traditionally for its nutritious and medicinal properties. Though assumptions traditionally suggest that it may also have an anticancer property, it is important to scientifically evaluate this property. The aim of this study is to ascertain if C. nucifera juice has an antproliferative effect. Methods: The study was carried-out on rapid proliferating seeds (Sorghum bicolor) and the mean radicle lengths (mm) was taken after 48 and 72 hours. Results: The control group had an unrestricted progressive proliferation throughout the study. Methotrexate elicited significant (P < 0.001) antiproliferative effect, with percentage inhibition of 73.9 and 87.6% after 48 and 72 hours. C. nucifera juice 20% v/v concentration gave significant (P < 0.01) inhibitory effect of 49.9% after 72 hours. C. nucifera juice 40% v/v gave a significant (P < 0.01) effect of 46% and a more significant (P < 0.001) effect of 49.7% after 48 and 72 hours. C. nucifera juice 60% v/v had high significant (P < 0.001) activity after 48 and 72 hours, giving inhibitory effect of 55.3% and 80%, respectively. C. nucifera juice and methotrexate combination had a good synergic effect, eliciting significant (P < 0.001) inhibitory effect of 73.4% and 80% after 48 and 72 hours, respectively. Conclusion: The experimental results have unveiled that C. nucifera juice has a potential for eliciting antiproliferative effect.